Prediction of mental strength from the satisfaction of basic needs in CABA and GBA esports players - Pablo Christian González Caino (Interacciones)
Background: Esports are here to stay. Previous studies have shown that sports athletes have characteristics Esports are here to stay. Previous studies have shown that esports athletes have similar characteristics, such as satisfaction from competing, as those in traditional sports. However, being an area still growing, few studies have addressed them in Latin America. This study aimed to determine the relationship and predictors of mental toughness from the satisfaction of basic needs in amateur esports players from the Autonomous City of Buenos Aires and Greater Buenos Aires, Argentina. Methods: For this, a sample of 426 participants (85% male) was constituted, with a mean age of 22 years (SD = 3.67), who answered the Basic Needs Satisfaction in Sport Scale (BNSSS) and the Mental Toughness Index (MTI) questionnaire, as well as a sociodemographic questionnaire. Results: The results indicated a strong relationship between both variables, especially with the dimensions of competence satisfaction and perception of choice, also being the main predictors of mental strength. Conclusions: These results provide new empirical evidence for this area in formation, as well as different issues to be taken into account to develop mental strength and sporting success in esports.